Unemployment and access to health care - Ilić, Boris (Array, 2019)
Introduction. At the time of the global economies’ recovery from the effects of fourth major recession after the Second World War, there was a major increase in the unemployment rate that created a significant existential and public health challenge Aim. The aim of this study was to provide a systematic review of available research on effects of unemployment on access to health care, and consequentially on health of the population. Methods. A systematic search of relevant, peer-reviewed electronic databases was conducted to identify systematic reviews, review articles, original research papers and reports for the period of past ten years. Results. 10.234 results were initially identified, five of which were included in this review. Conclusion. Significant number of studies confirms that the unemployed individuals, due to sometimes limited access to health care, have impaired health in comparison to the employed population, both in physical and mental health. Global economic change will have a stronger impact on the health of the population in poor countries, therefore a fair and comprehensive system of health care for the unemployed is of paramount importance for the purpose of preserving the health of the population.